2019
DOI: 10.1177/0954406219866883
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on a fully thermoplastic composite subjected to repeated impacts

Abstract: In the last years, the spread of composite laminates into the engineering sectors was observed; the main reason lies in higher values of strength/weight and stiffness/weight ratios with respect to conventional materials. Firstly, the attention was focused on fibres reinforced with thermosetting matrix. Then, the necessity to move towards low density and recyclable solutions has implied the development of composites made with thermoplastic matrix. Even if the first application of thermoplastic composites can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…When plastic deformation is caused by successive impacts, absorbed energy decreases, but when tape breaking begins, absorbed energy increases. This result is contrary to what was previously observed by researchers using thermosetting composites [85,86].…”
Section: Resin Effectscontrasting
confidence: 99%
See 1 more Smart Citation
“…When plastic deformation is caused by successive impacts, absorbed energy decreases, but when tape breaking begins, absorbed energy increases. This result is contrary to what was previously observed by researchers using thermosetting composites [85,86].…”
Section: Resin Effectscontrasting
confidence: 99%
“…Thicker samples require more impacts in order to penetrate [92]. The flexural stiffness is defined both by thickness and panel dimensions, smaller sized impact samples can be combined with interlaminar shear strength determination tests to assess the post-impact strength retention properties [86].…”
Section: Laminate Thicknessmentioning
confidence: 99%
“…[19][20][21] Boria et al performed a thorough empirical investigation of the mechanical properties of a PP-based composite laminate under repeated LVI scenarios. 22 It was concluded that modifying the resin materials can govern the impact perforation energy, damage propagation, and permanent after-impact deformation of composite plates. 23,24 Moreover, inspecting the impacted samples introduces the matrix plasticization and straining of the whole yarn as the primary energy-absorbing mechanisms within the thermoplastic-based Glass composites.…”
Section: Introductionmentioning
confidence: 99%
“…Although repeated impacts are not uncommon in real-world applications of composites [9,10], there are not many studies in the literature addressing that, either numerically-or experimentally-based, as most focus on multiple hits at the same point [11]. The studies on the repeated impact behavior of composites mostly concern repeated impact at the same location by considering different impactor or target features, such as impactor geometry [12][13][14] and mass [15], reinforcement type [16][17][18][19], laminate thickness [17,20], and stacking sequence [21,22]. Atas et al [23] investigated the effect of thickness on the repeated low-velocity impact response of E-glass/epoxy composites reporting the energy profiling diagram and the perforation limit.…”
Section: Introductionmentioning
confidence: 99%